MISTAKE ANALYSIS OF MA STUDENTS SOLVE MATH MATHEMATICS ON POLYNOMIAL MATERIALS - Rani Oktaviani (Journal Of Educational Experts (JEE), 2020)
This research aims to determine (1) to find out the average percentage of each type of error in solving polynomial problems (2) to find out the type of error most done by students in solving polynomial problems. The subjects of this study were all students of class XII in one MA in Cimahi City in the 2019/2020 school year, totaling 22 people. This research uses a qualitative approach and descriptive method. The results of this study indicate the type of error is the largest operation error, this is because students are less thorough and in a hurry in the calculation process. Meanwhile, generally the thing that causes students to make mistakes is not understanding the concept by writing incorrect formulas, procedures / steps that are used less precisely, and not careful when performing operations.